2018
DOI: 10.1080/10669817.2018.1533195
|View full text |Cite
|
Sign up to set email alerts
|

The C0-C2 axial rotation test: normal values, intra- and inter-rater reliability and correlation with the flexion rotation test in normal subjects

Abstract: Objectives: Impairment in upper cervical spine mobility is associated with cervicogenic headache severity and disability. Measures of such mobility include the flexion-rotation test (FRT), which requires full cervical flexion and may be influenced by lower cervical spine dysfunction. The C0-C2 axial rotation test also evaluates upper cervical mobility but normal values and reliability have not been reported. Our objective is to determine normal values, and intra-rater and inter-rater reliability of the C0-C2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 26 publications
2
26
2
1
Order By: Relevance
“…A recent in vivo study showed that the exion-extension of C1-2 was 13.7 ± 4.2°, accounting for 14.5% of the overall exion-extension ROM; the lateral bending neck motion of C1-2 was 7.6 ± 2.7°, accounting for 13.2% of the overall lateral bending ROM; and the axial torsion neck motion of C1-2 was 72.9 ± 7.6°, accounting for 73.2% of the overall rotation ROM [22]. Previous investigations also achieved similar results [23,24,25]. Once the motion of C1-2 joint is restricted by the anterior continuous bony bridge, the bearing force capacity from the skull and the neck is in turn reduced, which further increases the risk of cervical fracture.…”
Section: Declarationssupporting
confidence: 58%
“…A recent in vivo study showed that the exion-extension of C1-2 was 13.7 ± 4.2°, accounting for 14.5% of the overall exion-extension ROM; the lateral bending neck motion of C1-2 was 7.6 ± 2.7°, accounting for 13.2% of the overall lateral bending ROM; and the axial torsion neck motion of C1-2 was 72.9 ± 7.6°, accounting for 73.2% of the overall rotation ROM [22]. Previous investigations also achieved similar results [23,24,25]. Once the motion of C1-2 joint is restricted by the anterior continuous bony bridge, the bearing force capacity from the skull and the neck is in turn reduced, which further increases the risk of cervical fracture.…”
Section: Declarationssupporting
confidence: 58%
“…Although it is considered a test to assess the rotation of the C1-2 segment, the presence of painful joints in the lower cervical spine reduced the available range in the flexion-rotation test to 37.5° [ 10 ]. This indicates that lower cervical spine pain may reduce the ROM recorded during the flexion-rotation test [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, with a sample size comparable to ours (upper ( n =21) and lower (n=15)), Treleaven et al showed comparable results with the joint position error test. A second reason could also be that the “axial rotation test” described by Satput et al (2019) [ 80 ] is not accurate enough and that some patients classified as having upper cervical spine pain were not.…”
Section: Discussionmentioning
confidence: 99%